Advice to Clinicians on Communication from Adolescents and Young Adults with Cancer and Parents of Children with Cancer - Meghana Srinivas; Erica C. Kaye; Lindsay J. Blazin; Justin N. Baker; Jennifer W. Mack; James M. DuBois; Bryan A. Sisk (MDPI AG, 2022)
Effective communication is integral to patient and family-centered care in pediatric and adolescent and young adult (AYA) oncology and improving healthcare delivery and outcomes. There is limited knowledge about whether AYAs and parents have similar communication preferences and needs. By eliciting and comparing communication advice from AYAs and parents, we can identify salient guidance for how clinicians can better communicate. We performed secondary analysis of semi-structured interviews from 2 qualitative communication studies. In one study, 80 parents of children with cancer during treatment, survivorship, or bereavement were interviewed. In the second study, AYAs with cancer during treatment or survivorship were interviewed. We asked AYAs and parents to provide communication advice for oncology clinicians. Using thematic analysis, we identified categories of advice related to three overarching themes: interpersonal relationships, informational preferences, and delivery of treatment, resources, and medical care. AYAs and parents provided similar advice about the need for compassion, strong connections, hopefulness, commitment, and transparent honesty However, AYAs placed additional emphasis on clinicians maintaining a calm demeanor.